Novel approach to detect hate speech and profanity on online platforms - Pritha, Barha Meherun; Islam, Samin; Alam, Tabassum (Brac University, 2022)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2021.